A95 DO BENIGN LIVER TUMOURS ALWAYS STAY BENIGN? A CASE REPORT OF HEPATIC INFLAMMATORY PSEUDOTUMOR AND SUBSEQUENT CHOLANGIOCARCINOMA. (26th February 2020) - Onizuka, K; Schell, M; Tsoi, K
Abstract: Background: Hepatic inflammatory pseudotumors (HIPTs) are rare, benign lesions of unclear etiology which can be challenging to diagnose and differentiate from malignant processes. The optimal treatment and follow up of these lesions is controversial, and literature exists to support both surgical resection as well as conservative medical management. The natural history of HIPTs is generally benign, however there are some reports of disease recurrence, and two reports of malignant transformation to lymphoma. Aims: To describe a case of HIPT with progression to malignancy. Methods: Case report and review of the literature. Results: A 53-year-old male presented to St. Joseph's Healthcare Hamilton in August 2019 with a three-week history of abdominal pain and distention. He had a previous diagnosis of HIPT, incidentally found on ultrasound four years earlier. CT in January 2016 reported two well-marginated focal liver masses with peripheral rim enhancement and central hypodensity, 3.9 x 3.9cm in segment 2, and a 6 x 4.6cm central lesion, as well as diffuse fatty infiltration of the liver. Bloodwork showed a mildly elevated Ca19-9 626 kU/L, and normal CEA and AFP. Two biopsies were performed in 2016, both demonstrating dense fibrous tissue and abundant chronic inflammatory cell infiltrate composed of lymphocytes, histiocytes, eosinophils, and plasma cells, with some areas of bland spindle cell proliferation. No malignant cells, and histology was felt to be consistent with HIPT. MRI in September 2017 showed progression of disease, prompting Rheumatology to initiate immunosuppressive medications, however serial imaging continued to show increase in the size and number of lesions. Upon presentation to hospital in August 2019 ultrasound showed new ascites, with ascitic fluid analysis reporting highly atypical cells with prominent nucleoli of uncertain origin. CT showed extensive intrahepatic lesions throughout both lobes of the liver, and tumor markers were elevated with Ca19-9 16, 581 kU/L, CEA 10 ug/L, Ca125 511 kU/L, and normal AFP. Repeat liver biopsy reported adenocarcinoma, likely cholangiocarcinoma, with background cirrhosis. Medical oncology did not feel he would tolerate chemotherapy, and he was thus discharged home with palliative supports. Conclusions: HIPTs are benign lesions that are often initially misdiagnosed as malignancy, however this is the first case reporting progression of HIPT to cholangiocarcinoma. It is unclear if HIPT itself has premalignant potential, or whether its presence delays diagnosis of subsequent de novo malignancies. Given these uncertainties, as well as the lack of clarity on optimal management of HIPT, this case illustrates the importance of long-term clinical and radiographic follow up of these uncommon lesions, with consideration of repeat biopsy if the disease is not following the expected clinical course. Funding Agencies: None